USE MODEL TYPE COOPERATIVE LEARNING JIGSAW TO INCREASE ACTIVITY AND RESULTS OF LEARNING PUPILS SUBJECT SOCIAL STUDIES CLASS IV SD STATE 1 SUKANEGARA - Sudrajat, Mulat (STIT AL MULTAZAM, 2017)
This research is motivated by the activity and student learning outcomes are still low in the fourth grade of SD Negeri 1 Sukanegara particularly in social studies. Therefore, the purpose of this study to increase the activity and results of social studies using a model of the type cooperative learning jigsaw. The research methodology using Classroom Action Research (PTK) with three cycles and each cycle through the four stages, namely planning (planning), action (acting), observations (observating) and reflection (reflecting). Data collection techniques in this study is the observation of activity and achievement test, the data collection instrument uses observation sheets and test questions. The results using this jigsaw type of cooperative learning, showed an increase in activity and student learning outcomes. increased in each cycle, namely 63.47 in the first cycle, increasing to 66.21 in the second cycle. Thus, the use of cooperative learning model of jigsaw type can increase the activity and learning outcomes in social studies fourth grade students of SD Negeri 1 Sukanegara.